A practice theory perspective on learning: beyond a 'standard' view. Issue 3 (2nd September 2021) - Kemmis, Stephen
ABSTRACT: In this essay, I explore a disagreement with my friend Theodore (Ted) Schatzki about learning. Specifically, the dispute is between views of learning presented in the (2017) book edited by Peter Grootenboer, Christine Edwards-Groves and Sarojni Choy, Practice Theory Perspectives on Pedagogy and Education: Praxis, diversity, and contestation, specifically Schatzki's 'Chapter 2: Practices and learning' and Kemmis, Edwards-Groves, Lloyd, Grootenboer, Hardy and Wilkinson 'Chapter 3: Learning as being 'stirred in' to practices'. Schatzki thinks practice theory can accept the 'standard' view of learning as the acquisition of knowledge. I aim to secure an alternative view: that practice theory offers a different conception of learning as happening in the reproduction (with variation) and transformation of practices, and the production of new practices – but the argument also leads me to conclude that learning itself is not a practice.